Pengobatan Alternatif Sebagai Upaya Penyembuhan Penyakit - Andira, Dwi Ayu; Pudjibudojo, Jatie K. (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2020)
In modern times, variety of advanced technologies have been present in various fields, one of which is health. Rapid developments in the health sector include medical care. Medical treatment experiences a lot of progress that give hope for the patient's recovery. This certainty is because medical treatment has been considered a rational and scientific treatment. On the other hand, in reality there are still many patients who use alternative medicine. Patients have trust or believe that alternative medicine is a treatment that can healing their illness because they have economical prices, minimal side effects and are easy to find. The purpose of this literature study is to find out the reasons for patients in choosing alternative medicine as an effort to healing the disease. So that alternative medicine is chosen by patients to try to healing diseases other than using medical treatment.